Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Rewrite the formula to make \( s \) the subject:

[tex]\[ s = \sqrt{\frac{x^2 b c}{s - a}} \][/tex]


Sagot :

Sure, let's make \( s \) the subject of the formula in the given equation:

[tex]\[ x = \sqrt{\frac{s(s - a)}{b c}} \][/tex]

We will solve this step-by-step.

### Step 1: Remove the square root by squaring both sides
First, square both sides of the equation to eliminate the square root on the right-hand side.

[tex]\[ x^2 = \left(\sqrt{\frac{s(s - a)}{b c}}\right)^2 \][/tex]

[tex]\[ x^2 = \frac{s(s - a)}{b c} \][/tex]

### Step 2: Isolate the term involving \( s \)
Next, multiply both sides of the equation by \( b c \) to isolate the term involving \( s \) on one side.

[tex]\[ x^2 \cdot b c = s(s - a) \][/tex]

[tex]\[ b c x^2 = s^2 - a s \][/tex]

### Step 3: Bring all terms to one side
Rearrange the equation to bring all terms to one side, setting it up as a quadratic equation in \( s \).

[tex]\[ s^2 - a s - b c x^2 = 0 \][/tex]

### Step 4: Solve the quadratic equation
To solve the quadratic equation \( s^2 - a s - b c x^2 = 0 \), we use the quadratic formula:

[tex]\[ s = \frac{-B \pm \sqrt{B^2 - 4AC}}{2A} \][/tex]

For our equation \( s^2 - a s - b c x^2 = 0 \), the coefficients are:
\( A = 1 \), \( B = -a \), and \( C = -b c x^2 \).

Substitute these values into the quadratic formula:

[tex]\[ s = \frac{-(-a) \pm \sqrt{(-a)^2 - 4(1)(-b c x^2)}}{2(1)} \][/tex]

[tex]\[ s = \frac{a \pm \sqrt{a^2 + 4 b c x^2}}{2} \][/tex]

### Step 5: Simplify the solutions
Now, simplify the expression to get the final solutions for \( s \):

[tex]\[ s = \frac{a + \sqrt{a^2 + 4 b c x^2}}{2} \quad \text{or} \quad s = \frac{a - \sqrt{a^2 + 4 b c x^2}}{2} \][/tex]

### Conclusion
Therefore, the solutions for \( s \) in terms of \( x \) are:

[tex]\[ s = \frac{a + \sqrt{a^2 + 4 b c x^2}}{2} \quad \text{and} \quad s = \frac{a - \sqrt{a^2 + 4 b c x^2}}{2} \][/tex]

So, we have found two possible values for \( s \) as functions of \( a \), \( b \), \( c \), and \( x \):

[tex]\[ s = \frac{a + \sqrt{a^2 + 4 b c x^2}}{2} \][/tex]

[tex]\[ s = \frac{a - \sqrt{a^2 + 4 b c x^2}}{2} \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.